Roman Law and the Origins of the Civil Law Tradition - Mousourakis, George (Springer, 2016)
This unique publication offers a complete history of Roman law, from its early beginnings through to its resurgence in Europe where it was widely applied until the eighteenth century. Besides a detailed overview of the sources of Roman law, the book also includes sections on private and criminal law and procedure, with special attention given to those aspects of Roman law that have particular importance to today's lawyer. The last three chapters of the book offer an overview of the history of Roman law from the early Middle Ages to modern times and illustrate the way in which Roman law furnished the basis of contemporary civil law systems. In this part, special attention is given to the factors that warranted the revival and subsequent reception of Roman law as the ‘common law’ of Continental Europe. Combining the perspectives of legal history with those of social and political history, the book can be profitably read by students and scholars, as well as by general readers with an interest in ancient and early European legal history.